Temporally resolved thermal desorption of volatile organics from nanoporous silica preconcentrator. Issue 1 (9th November 2020) - Winter, William; Day, Coco; Prestage, Joshua; Hutter, Tanya
Abstract : Gas-phase volatile organic compounds (VOCs) are collected in a nanoporous silica preconcentrator, then released slowly by heating onto a detector. Desorption temperature depends on VOC properties, allowing potential discrimination. Abstract : Detection and separation of gas-phase volatile organic compounds (VOCs) is of great importance for many applications including air quality monitoring, toxic gas detection and medical diagnostics. A lack of small and low-cost detectors limits the potential applications of VOC gas sensors, especially in the areas of consumer products and the 'Internet of Things'. Most of the commercially available low-cost technologies are either only capable of measuring a single VOC type, or only provide a total VOC concentration, without the ability to provide information on the nature or type of the VOC. We present a new approach for improving the selectivity of VOC detection, based on temporally resolved thermal desorption of VOCs from a nanoporous material, which can be combined with any existing VOC detector. This work uses a nanoporous silica material that adsorbs VOC molecules, which are then thermally desorbed onto a broadband VOC detector. Different VOCs are desorbed at different temperatures depending on their boiling point and affinity to the porous surface. The nanoporous silica is inert; VOC adsorption is proportional to the concentration of VOC in the environment, and is fully reversible. An example of a detection system using a commercial total VOC photoionization detector and a nanoporous silica preconcentrator is demonstrated here for six different VOCs, and shows potential for discrimination between the VOCs.